Targeting BRD4 ameliorates experimental emphysema by disrupting super-enhancer in polarized alveolar macrophage - Difei Li; Xing Shi; Yuqiong Yang; Yao Deng; Dandan Chen; Shuyu Chen; Jinyong Wang; Guanxi Wen; Zhenyu Liang; Fengyan Wang; Jiaqi Gao; Yuanyuan Liu; et al. (Respiratory Research)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a progressive chronic lung disease characterized by chronic airway inflammation and emphysema. Macrophage polarization plays an important role in COPD pathogenesis by secreting inflammatory mediators. Bromodomain-containing protein 4 (BRD4), an epigenetic reader that specifically binds to histones, plays a crucial role in inflammatory diseases by regulating macrophage polarization. Herein, we attempted to examine the hypothesis that modulating alveolar macrophage polarization via BRD4 inhibitors might has a potential for COPD treatment. Methods We firstly analyzed BRD4 expression and its correlation with clinical parameters and macrophage polarization markers in sputum transcriptomes from 94 COPD patients and 36 healthy individuals. In vivo, BRD4 inhibitor JQ1 and degrader ARV-825 were intraperitoneally administrated into emphysema mice to assess their effects on lung emphysema and inflammation. In vitro, RNA-seq and CUT&Tag assay of BRD4 and H3K27ac were applied for elucidating how BRD4 regulates macrophage polarization. Results We found an increased expression of BRD4 in the induced sputum from patients with COPD and unveiled a strong correlation between BRD4 expression and clinical parameters as well as macrophage polarization. Subsequently, BRD4 inhibitor JQ1 and degrader ARV-825 significantly mitigated emphysema and airway inflammation along with better protection of lung function in mice. BRD4 inhibition also suppressed both M1 and M2 alveolar macrophage polarization. The CUT&Tag assay of BRD4 and H3K27ac, revealed that BRD4 inhibition disrupted the super-enhancers (SEs) of IRF4 (a crucial transcription factor for M2 macrophage), and subsequently affected the expression of matrix metalloproteinase 12 (MMP12) which is vital for emphysema development. Conclusion This study suggested that downregulation of BRD4 might suppress airway inflammation and emphysema through disrupting the SEs of IRF4 and alveolar macrophages polarization, which might be a potential target of therapeutic intervention in COPD. A diagram of the mechanism by which BRD4 mediated super-enhancer of IRF4 in M2 AMs. Graphic illustration showed targeting BRD4 in M2 polarized AMs lead to the downregulation of MMP12 expression, resulting in the amelioration of experimental emphysema by disrupting the super-enhancer of IRF4. Graphical abstract